Paul Bunyan, a Tall Tale - Kellogg, Steven (New York : W. Morrow, 1984)
Recounts the life of the extraordinary lumberjack whose unusual size and strength brought him many fantastic adventures.
Keywords: Bunyan, Paul (Legendary character) -- Juvenile literature